Analisis Pengaruh Budaya Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan pada Industri Kertas Daur Ulang CV Kridasana (Survey pada Bagian Produksi) - Imas Komariyah; Kania Laelawati (Manajemen dan Pariwisata, 2023)
This study aims to analyze the influence of work culture and work discipline on employee work productivity in the recycled paper industry of Kridasana, especially in the production department. The method used is a survey with a sample of 30 respondents from the total population of production department employees. The results show that work culture has a significant influence on employee work productivity in the recycled paper industry of Kridasana. In addition, work discipline also has a significant influence on employee work productivity in the industry. This indicates that positive work culture and good work discipline can improve employee work productivity in the recycled paper industry of Kridasana. The conclusion of this study is that work culture and work discipline are important factors in improving employee work productivity in the recycled paper industry of Kridasana, especially in the production department. Therefore, the company must pay attention to and improve work culture and work discipline of employees in order to increase work productivity and achieve better company goals in the future.